A mixed methods evaluation of the Paediatric Musculoskeletal Matters (PMM) online portfolio - Nicola Smith; Helen E. Foster; Sharmila Jandial (BMC, 2021)
Abstract Background The PMM Portfolio is comprised of the Paediatric Musculoskeletal Matters (PMM) website, the paediatric Gait, Arms, Legs and Spine (pGALS) app and e-learning modules (ELM). The target audiences are non-specialists in paediatric musculoskeletal medicine. Our study aimed to evaluate impact on learning and clinical practice. Methods Mixed methods (analytics, online survey, interviews) were used with PMM and ELM registered users and purposive sampling of users using international contacts within paediatrics and paediatric rheumatology. Data was analysed using descriptive statistics and qualitative techniques. A Paired T-Test compared self-rated confidence before and after use of the PMM Portfolio. Results There has been wide reach for all the e-resources; PMM website (662,827 hits, 262,476 users, 214 countries, data 31st July 2020); pGALS app (12,670 downloads, 70 countries, data 31st July 2020); ELM (150 users, 30 countries, data 30th May 2019). There were 164 responses (students, trainees and health care professionals) to the survey from 25 countries. Most responders deemed the PMM Portfolio useful / very useful for their learning with significantly increased self-rated confidence in their clinical examination and reasoning skills following access to the PMM website, p = < 0.01, pGALS app, p = < 0.01 and ELM, p = < 0.01. The most popular PMM website pages related to clinical assessment techniques (especially pGALS). There was high uptake of the pGALS app and pGALS ELM especially from trainees and allied health professionals. Many clinicians reported the PMM Portfolio to be useful when used to teach others. User feedback reported that easy navigation, open access, clinical images and cases were the most valued features. User feedback highlighted need to increase awareness of the e-resources through training programmes. Conclusions The PMM Portfolio was developed to aid learning for clinicians who are not specialists in paediatric MSK medicine. Our evaluation demonstrates wide international reach and positive feedback on learning. The PMM Portfolio is a highly useful e-resource for paediatric rheumatologists in their teaching of others to raise awareness, facilitate early diagnosis and referral of children with suspected disease. The wide user engagement informed future PMM Portfolio development and the mixed method of evaluation is transferable to other e-resources.